Assessment of Spatial Variability in Some Soil Properties as Related to Soil Salinity and Alkalinity in Bafra Plain in Northern Turkey - Cemek, Bilal; Guler, Mustafa; Kilic, Kenan; Demir, Yusuf; Arslan, Hakan (Springer, 2007)
The objectives of this study were to assess the variability in soil properties affecting salinity and alkalinity, and to analyze spatial distribution patterns of salinity (EC) and alkalinity (ESP) in the plain, which was used irrigation agriculture with low quality waters. Soil samples were collected from 0-30crn, 30-60cm, 60-90cm and 90-120cm soil depths at 60 sampling sites. Soil pH had the minimum variability, and hydraulic conductivity (Ks) had the maximum variability at all depths. The mean values of pH, EC, ESP and Ks increased while the mean values of CEC decreased with soil depth. Values pH, EC and ESP were generally high in the east and northeastern sides. Soil properties indicated moderate to strong spatial dependence. ESP and pH were moderately spatially dependent for three of the four depths, EC exhibited moderate spatial dependence for one of the four depths, CEC had a moderate spatial dependence at all depths, and Ks exhibited a strong spatial dependence. EC, CEC, and ESP were considerably variable in small distances. The spatial variability in small distances of EC, CEC, pH and ESP generally increased with depth. All gcostatistical range values were greater than 1230 m. It was inferred that the strong spatial dependency of soil properties would be resulted in extrinsic factors such as ground water level, drainage, irrigation systems and microtopography.
Arslan, Hakan/0000-0002-9677-6035; , Kenan/0000-0002-8205-3717;
Keywords: Spatial Variability; Geostatistics; Bafra Plain; Soil Salinity